2D dynamic structure-soil-structure interaction: A case study of Millikan Library Building. (April 2020) - Han, Bing; Chen, Shaolin; Liang, Jianwen
Highlights: A case study to investigate SSSI effects with large separation distance using 2D anti-plane model and in-plane model. The adjacent building may amplify or reduce structural response obviously, which may be up to 40% and 30%, respectively. The SSSI effects may persist up to large separation distance (the amplification is 36% when distance is 410 m in some case). Abstract: Dynamic structure-soil-structure interaction (SSSI) effects with large separation distance are investigated based on a case study of Millikan Library Building. The numerical results are obtained by two-dimensional (2D) anti-plane model and in-plane model using indirect boundary element method (IBEM) for any incident direction of seismic waves. It's shown that the SSSI effects may be detrimental or beneficial, and the amplification and reduction of structural response compared to the stand-alone structure may be up to 40% and 30%, respectively in the case of Millikan Library Building. The structural response is sensitive to adjacent building's parameters. Both for anti-plane model and in-plane model, more similar or heavier adjacent building has more significant influence. Moreover, beyond what was previously known, the SSSI effects may persist up to large separation distance, e.g., the amplification may be up to 36% when separation distance is up to b / λ equ ≈ 2.5 ( b ≈ 410 m). Of course, the detrimental or beneficial effects are not constant but appear alternately with variation of the separation distance, which should be considered comprehensively in the prediction of seismic response for design.